Sistem Pendukung Keputusan Dalam Menentukan Pengguna Listrik Subsidi Dan Nonsubsidi Menggunakan Metode Fuzzy Mamdani (Studi Kasus : PT. PLN Tanjung Balai) - Adi Widarma; Hana Kumala (Universitas Asahan, 2018)
Abstract - The electricity subsidy program is one of the poverty reduction programs by providing electricity subsidies to poor and disadvantaged households paid by the Government of Indonesia to PT. PLN (Persero). At PT. PLN (Persero) Area Rantau Prapat Rayon Tanjung Balai which is located on Jl. General Sudirman has a problem that is faced, namely regarding the subsidy budget, it turns out that there have been many wrong targets, most of the subsidy funds have fallen to economically capable people. The government applies the electricity subsidy policy on target, subsidies must be really enjoyed by poor people. To provide electricity subsidies to poor households and poor households, both humans and agencies cannot be separated from information technology systems. This system is usually called a decision support system that is designed to assist in making a decision where no one knows exactly how the decision should be made. The problem of decision-making systems using fuzzy logic systems is very suitable for definite reasoning or estimation, especially for systems with difficult mathematical models and inappropriate data to get a definite decision. Keywords - Decision Support System, Electricity Subsidies, Fuzzy Logic.